Steve Jobs [videorecording (DVD)] - Fassbender, Michael, 1977-; Winslet, Kate; Rogen, Seth, 1982-; Daniels, Jeff, 1955-; Isaacson, Walter (Universal Studios Home Entertainment, 2016)
Steve Jobs takes us behind the scenes of the digital revolution to paint a portrait of the man at its epicenter. The story unfolds backstage at three iconic product launches, ending in 1998 with the unveiling of the iMac.